A novel delivery vehicle for copper peptides. (29th November 2022) - Liu, Tianqi; Hu, Lu; Lu, Beibei; Bo, Yiyang; Liao, Ya; Zhan, Jingbo; Pei, Yunlin; Sun, Huaiqing; Wang, Zhenyuan; Guo, Chaowan; Zhang, Jiaheng
Abstract : Preparation of green ionic liquid using natural alkaloids and organic acids for efficient transdermal delivery of GHK-Cu. Abstract : While glycyl-l -histidyl-l -lysine-copper (GHK-Cu) has a variety of biological functions, it is not easily absorbed by skin directly, which along with several contraindications, greatly limit its clinical use. We developed an ionic-liquid-based delivery vehicle composed of betaine and tartaric acid to address the difficulties associated with the use of GHK-Cu. The prepared ionic liquid is safe, stable, and able to deliver a high GHK-Cu drug-loading capacity while maintaining the activity of GHK-Cu and ensuring its biological functions. In addition, it substantially improves the permeability of GHK-Cu to deeper skin layers. The ionic-liquid delivery vehicle, which was developed by combining experimental and theoretical studies, provides a simple, low-cost, and effective method for applying GHK-Cu while providing design ideas for active peptides in general.